To determine when the equation \(-5 = \frac{4 - 3}{x^4 - 3x}\) is undefined, we need to analyze the denominator \(x^4 - 3x\).
The expression is undefined when the denominator equals zero:
\[ x^4 - 3x = 0 \]
We can factor out \(x\):
\[ x(x^3 - 3) = 0 \]
Setting each factor to zero gives us:
- \(x = 0\)
- \(x^3 - 3 = 0 \Rightarrow x^3 = 3 \Rightarrow x = \sqrt[3]{3}\)
Thus, the values that make the equation undefined are \(x = 0\) and \(x = \sqrt[3]{3}\).
Now, none of the provided answers \(-\frac{4}{3}\), \(-\frac{3}{4}\), \(\frac{4}{3}\), or \(\frac{3}{4}\) are equal to either of those values.
Therefore, none of the provided options directly lead to the equation being undefined, since it is undefined at \(x = 0\) and \(x = \sqrt[3]{3}\).
If I need to select only from the provided responses, they do not represent any values that cause the equation to be undefined.